Gender differences in the implementation of school-based assessment in a Malaysian state - Veloo, Arsaythamby; Md Ali, Ruzlan; Krishnasamy, Hariharan N. (InScience Press, 2016)
This study aims to identify the differences in assessment knowledge, school support, teacher readiness, teacher skills and challenges faced by male and female Grade 8 teachers who are involved in implementing School-Based Assessment (SBA) and the interrelationship among these five factors. In addition, this study explores the teachers’ views with regards to these five factors.This study uses a quantitative questionnaire designed by the researchers, and a total of 243 Grade 8 teachers answered the questionnaire.Qualitative data was then collected via semi-structured interviews which were conducted with 20 teachers. The findings show that male teachers are more ready to implement SBA compared to female teachers.Compared to the female teachers, the male teachers view school support as more important. In terms of knowledge, skills and challenges towards the implementation of SBA, there are no gender differences. The findings also show that there exist significant relationships among the five factors except between school support and challenges faced in SBA.Although male and female teachers share many similar views, the predominant view among female teachers when compared to the male teachers is that many challenges and issues need to be addressed in the implementation of SBA. The findings from the interviews also suggest that male teachers are more willing to accept changes when compared to the female teachers.This study has implications for the implementation of SBA in Malaysia because 63% of the teachers implementing SBA are females.